A Bibliometric Exploration of Sustainable Tourism Destinations: Trends, Perspectives, and Future Directions - Risda, Irfan Taufik (Cita konsultindo, 2025)
Sustainable tourism has become a focal point for governments, stakeholders, and academics, recognizing its role in promoting environmentally friendly and responsible development. The tourism industry, encompassing hotels, transportation, restaurants, and travel services, has made significant strides in adopting sustainable practices. However, comprehensive attention to destination management remains limited, largely due to the complexity of its elements. This study aims to systematically examine research on sustainable tourism destinations from 2012 to 2022 using Scopus data. A descriptive qualitative approach, combining bibliometric analysis and literature review, was employed. The study analyzed 200 international publications in English, sourced from the Scopus database with the keyword